2021
DOI: 10.1620/tjem.253.159
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Disaster Medicine during Ten Years after the 2011 Great East Japan Earthquake

Abstract: The 2011 Great East Japan Earthquake (GEJE) has renewed the paradigm of disaster medicine. The Tohoku Journal of Experimental Medicine (TJEM) widened its scope to include the disaster science from the health perspectives. TJEM has been accumulating 76 articles related with "disaster" or "pandemic" out of which 69 were published after 2011. Tohoku University established the International Research Institute of Disaster Science (IRIDeS) that took initiative to impact the Sendai Framework for Disaster Risk Reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…The current study is consistent with the concept of disaster risk presented by Egawa et al (2017) and Egawa (2021), and could be reflected as the results of the hazard size. A previous study also reports a correlation between the number of completely collapsed houses and the number of mortalities due to collapsed houses in inland earthquakes (Naito et al 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The current study is consistent with the concept of disaster risk presented by Egawa et al (2017) and Egawa (2021), and could be reflected as the results of the hazard size. A previous study also reports a correlation between the number of completely collapsed houses and the number of mortalities due to collapsed houses in inland earthquakes (Naito et al 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it is vital that the dental care team shares information in the event of a disaster to ensure that the necessary support is delivered to those who need it most. Egawa et al reported that disaster risks are related to the coping capacities of healthcare systems [ 48 , 49 ]. Therefore, it is critical that a system be created that is capable of delivering dental support to people affected by a large-scale disaster.…”
Section: Training Programs and Enhanced Cooperation Between Support T...mentioning
confidence: 99%
“…Therefore, in Japan, medical exposure exceeds exposure to natural radiation, indicating that high levels of medical exposure are remarkable worldwide. Japanese people experienced the Hiroshima and Nagasaki atomic bombings, the Tokaimura nuclear accident (the Japan Nuclear Fuel Conversion Co. criticality accident) [5], and the Fukushima Daiichi Nuclear Power Plant accident [6][7][8][9][10][11][12][13][14][15]; therefore, medical radiation exposure is likely to be of significant concern [16,17]. The Fukushima Daiichi Nuclear Power Plant accident was a nuclear disaster that affected a wide area of eastern Japan, and many people outside of Fukushima Prefecture also suffered from anxiety about disaster exposure.…”
Section: Introductionmentioning
confidence: 99%